2019
DOI: 10.29252/jhehp.5.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Applying Sunflower Residues as a Green Manure on Increasing Zn Concentration of Two Iranian Wheat Cultivars in a Pb and Cd Polluted Soil

Abstract: Journal homepage: www.zums.ac.ir/jhehp Background: This research was investigated to evaluate effect of applying sunflower residues as a green manure on increasing zinc (Zn) concentration of two Iranian wheat cultivars in a Pb and cadmium (Cd) polluted soil. Methods: Treatments included the application of sunflower residuals grown in a Znpolluted soil at two levels of 0 and 8 t/ha, two wheat cultivars in a soil contaminated with Pb (0, 400 and 800 mg Pb/kg soil) and Cd (0, 5 and 10 mg Cd/kg soil). After 7 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
2
1
0
2
Order By: Relevance
“…Previous studies have denoted the interactive effects of heavy metals on nutrients such as Fe or Zn [23], which is consistent with our findings. It is notable that although PGPR and AMF reduced the plant Pb concentration by increasing its Fe availability (interactive effect), the role of soil microorganism activities in increasing plant Pb resistance and phytoremediation efficiency cannot be overlooked.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Previous studies have denoted the interactive effects of heavy metals on nutrients such as Fe or Zn [23], which is consistent with our findings. It is notable that although PGPR and AMF reduced the plant Pb concentration by increasing its Fe availability (interactive effect), the role of soil microorganism activities in increasing plant Pb resistance and phytoremediation efficiency cannot be overlooked.…”
Section: Resultssupporting
confidence: 93%
“…Therefore, it could be concluded that the presence of PGPR significantly lowered the soil pH (0.2 unit) as opposed to the control soil. Previous studies have also denoted increased soil Pb availability due to the reduction of soil pH [16,23]. It is also notable that the primary concentrations of the heavy metals in the cow manure were lower than the standard values suggested by the US Environmental Protection Agency [24].…”
Section: Resultsmentioning
confidence: 91%
“…This comes as an expected result of the response to improving the soil with the necessary elements needed by the wheat crop, which helped in its healthy development and growth, thus improving yield and quality. The current results are consistent with (12,13), who mentioned that the wheat crop is suitable for cultivation under sunflower allelopathic stress. The results of the broad bean and flax crop response came to the exact opposite of the results achieved in the wheat crop, as shown in Tables 3 and 4.…”
Section: Crop Growth Parameterssupporting
confidence: 92%
“…Penambahan serasah pohon sebagai pupuk hijau bersamaan dengan pemberian pupuk anorganik memberikan hasil padi yang jauh lebih tinggi daripada pupuk anorganik saja (Hossain et al, 2007). Aplikasi seresah bunga matahari berpengaruh nyata terhadap peningkatan konsentrasi Zn tanaman dan dapat berguna sebagai cara yang cocok untuk meningkatkan konsentrasi Zn gandum yang tumbuh di tanah yang kekurangan Zn dan tercemar logam berat (Baghaie et al, 2019). Pupuk hijau dari tanaman Tithonia diversifolia terbukti mampu memperbaiki kualitas tanah dan meningkatkan hasil tanaman kembang kol dan tanaman melon (Pia et al, 2020).…”
Section: Pendahuluanunclassified
“…Seresah atau limbah tanaman secara umum dapat dimanfaatkan sebagai penyubur tanah atau untuk memulihkan kesehatan tanah. Pemanfaatan seresah atau sisa-sisa tanaman memiliki pengaruh yang signifikan terhadap peningkatan konsentrasi Zn tanaman dan dapat berguna sebagai cara yang cocok untuk meningkatkan konsentrasi Zn gandum yang tumbuh di tanah yang kekurangan Zn (Baghaie et al, 2019). Studi menunjukkan bahwa aplikasi pupuk hijau meningkatkan pertumbuhan, hasil dan parameter hasil yang sebanding dengan aplikasi pupuk NPK.…”
Section: Pembahasanunclassified